2021
DOI: 10.3389/fimmu.2021.729705
|View full text |Cite
|
Sign up to set email alerts
|

Progression on the Roles and Mechanisms of Tumor-Infiltrating T Lymphocytes in Patients With Hepatocellular Carcinoma

Abstract: Primary liver cancer (PLC) is one of the most common malignancies in China, where it ranks second in mortality and fifth in morbidity. Currently, liver transplantation, hepatic tumor resection, radiofrequency ablation, and molecular-targeted agents are the major treatments for hepatocellular carcinoma (HCC). Overall, HCC has a poor survival rate and a high recurrence rate. Tumor-infiltrating lymphocytes (TILs) have been discovered to play essential roles in the development, prognosis, and immunotherapy treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 113 publications
1
43
1
1
Order By: Relevance
“…Some traditional Chinese medicines serve an anti-tumor role in immunosuppressive tumor microenvironment through upregulating immune response [ 28 ]. Tumor-infiltrating lymphocytes, which can recognize tumor cells and provoke an anti-tumor response plays an active role in the survival of patients with hepatocellular carcinoma [ 29 ]. There are also reports the ratios of tumor‐infiltrating CD4 + /CD8 + are associated with the survival of the patients with HCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some traditional Chinese medicines serve an anti-tumor role in immunosuppressive tumor microenvironment through upregulating immune response [ 28 ]. Tumor-infiltrating lymphocytes, which can recognize tumor cells and provoke an anti-tumor response plays an active role in the survival of patients with hepatocellular carcinoma [ 29 ]. There are also reports the ratios of tumor‐infiltrating CD4 + /CD8 + are associated with the survival of the patients with HCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD4+CD25+Foxp3+ regulatory T cells (Tregs) play a immunosuppressive role in TME which contributes to HCC initiation and progression ( 48 ). CD3+, CD8+, activated NKs, and Foxp3+ T cells were also found to have a suppression function in HCC ( 49 ). Several included literatures demonstrated altered T cell subpopulations in patients after CIK cell infusions ( 26 , 28 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes . Heterogeneous subsets of T cells, including cytotoxic CD8 + T lymphocytes (CTLs) and CD4 + CD25 + FoxP3 + T regulatory lymphocytes (Tregs), have been identified to infiltrate HCC tumors [ 46 , 47 ]. Whereas CTLs exhibit anti-tumorigenic properties, Tregs promote immunosuppression [ 48 ].…”
Section: Components Of the Tme In Hccmentioning
confidence: 99%